Sistem Informasi Rekam Medis Puskesmas Kotaratu Berbasis Desktop - Aprilia Ningsi; Kristina Sara; Anastasia Mude (Jurnal Pendidikan Informatika (EDUMATIC), 2021)
The administrative process at kotaratu health center still uses manual means. So, it takes a long time in handling patient visits and making reports. The goal of the study was to build a desktop-based medical record information system using the Microsoft Visual Basic. Net Programming Language and MySQL as its database. Data collection techniques through interviews, observations and literature studies. Meanwhile, to develop software (system) with waterfall method, while testing uses blackbox-testing. Our findings are in the form of a desktop-based information system at Kotaratu health center. Furthermore, Blackbox-testing results show that all components in this system are running well, and all medical record data is stored in the database to provide a convenience in managing patient data, searching for medical records, managing medical records and making reports periodically.